Isolated Bradycardia During Aneurysmal Clipping: Rebleed or Trigeminocardiac Reflex? - Singh, Nidhi; Jangra, Kiran; Regmi, Sabina; Singh, Apinderpreet (Journal of Neuroanaesthesiology and Critical Care, 2020)
The most common cause of nontraumatic subarachnoid hemorrhage is the rupture of intracranial aneurysm. After initial bleed, the risk of rebleeding is highest in the early postictal period and this rebleed is strongly associated with poor neurological outcome. The major goal of anesthesia in these surgeries is to prevent the rebleed. If rebleeding occurs prior to the craniotomy, it results in the acute rise of intracranial pressure and usually presents as bradycardia and hypertension (Cushing’s reflex). Here we reported a case where rebleeding presented unusually as isolated bradycardia without associated hypertension and was mistaken as trigeminocardiac reflex. The surgeon was informed about the event and they planned to proceed. After craniotomy, despite all the efforts the brain was persistently tight and surgery could not be completed. Postoperative scan showed rebleeding and the patient died after a few days in ICU.We highlighted in this case report the fact that isolated transient bradycardia may also be the presentation of rebleed with closed cranial vault. It is not always necessary to see all the features of Cushing’s traid in every patient. If bradycardia occurs before the craniotomy, the surgeon should be notified, the severity of bleed should be assessed, and further management should be planned according to the severity of bleed.
Keywords: bradycardia; Cushing’s traid; intracranial aneurysm; rebleeding; trigeminocardiac reflex